O obecności dzieła św. Teofana Rekluza w polskiej refleksji = Saint Theophan the Recluse`s oeuvre and reception of his thought in Poland - Kroczak, Justyna (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
St. Theophan the Recluse (George Govorov, 1815-1894) has been remembered by theologians and researchers for his ascetic and moral writings that were original yet stayed within the tradition of Russian hesychasm. In teaching how to enter into a prayer dialogue with God, St. Theophan considered a moulding of one`s heart of the most important spiritual exercises; piety and turning one`s mind to God were seen as means to this end. In Poland, the work of this theologian is known not only in the Orthodox but also in the Catholic circles (Jan Pryszmont published a monograph about him in 1979).
Keywords: Teofan Rekluz (1815-1894); Święty z Wyszy; Filokalia; Pryszmont, Jan; Nikolski, Piotr (1858-1940); teologia prawosławna; Theophan the Recluse; Saint of Vysha; Philokalia; Orthodox theology